FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMEN PRIMER - Kencana, Richie; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2025)
This study aimed to find how the influence of liquidity, asset structure, leverage, and institutional ownership in manufacturing companies consumer non-cylicals sector were listed on Indonesia Stock Exchange for 2019-2022. The sample was selected using purposive sampling method with the final sample data of 37 companies. The data processing technique used multiple linear regression analysis assisted by the SPSS 27 program and Microsoft Excel. The results of this study indicated that liquidity had significant positive effect on profitability. Meanwhile, asset structure and institutional ownership have no significant negative effect on profitability, also leverage has no significant positive effect on profitability. The implication of this research is the management must monitor the liquidity ratio in the company in order to increase company’s profitability.